Temperature Effects on Jembrana Superficial Unit (JSU) Recombinant Protein Expression in Escherichia coli BL21 - Maelani, Imelda; Indriawati, Indriawati; Ismail, Yulia Sari; Mulyani, Riska; Syahfitri, Widya (JURNAL BIOSAINS, 2025)
The efficiency of expression of recombinant proteins in host cells depends on achieving proper protein folding, solubility, and biological activity. Critical environmental factors, including temperature, pH, nutrient availability, and inducer concentration, significantly influence protein yield, stability, and functionality. Optimizing these conditions is essential to minimize protein misfolding and aggregation, which can adversely affect expression efficiency and reduce bioactivity. This study aims to measure the effect of temperature on the growth of Escherichia coli BL21 harboring the recombinant JSU protein, derived from the ENV-SU gene of the Jembrana virus. A controlled laboratory experiment was conducted in which bacterial cultures were incubated at 25°C and 37°C under identical conditions, except for temperature. The results indicate a statistically significant difference in bacterial growth between the two temperature conditions (p = 0.08), suggesting that E. coli BL21 exhibits enhanced growth at 37°C compared to 25°C. The mean bacterial growth rate at 37°C was 1.756, whereas at 25°C, the average growth was 1.425, demonstrating that higher temperatures facilitate bacterial proliferation. However, due to the relatively small sample size, further validation with a larger dataset is required to confirm these findings. These findings highlight the critical role of temperature optimization in enhancing bacterial growth and improving recombinant protein production efficiency, emphasizing the need for further investigation with a larger dataset to validate the results. Keywords: recombinant protein; temperature; IPTG; Escherichia coli BL21; JSU construct.